A narrative of the captivity of Mrs. Johnson, containing an account of her sufferings during four years with the Indians and French. Together with an appendix, containing the sermons preached at her funeral, and that of her mother, with sundry other interesting articles. - Johnson, Mrs. (Susannah Willard), 1730-1810. (Lowell, D. Bixby, 1834)
Mode of access: Internet.